(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In this article, we examine the landscape of sexually transmitted diseases, their impact on individuals and communities, and current approaches to the prevention and management of these infections. By understanding the problems that STDs cause and the tools available for prevention, we can work to create healthier and safer environments for all people at risk of these infections.